1994
DOI: 10.1093/jn/124.4.485
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Activity Is Reduced in Epidermal Cells from Energy-Restricted SENCAR Mice ,

Abstract: Female SENCAR mice were pre-fed a control or 40% energy-restricted (ER) diet with energy removed from fat and carbohydrate, or a control, balanced high fat (BHF, with similar energy from fat and carbohydrate), 35% energy restricted from fat (HCR) or 35% energy restricted from carbohydrate (HFR) diet. Epidermal cells were isolated by trypsin digestion for measurement of protein kinase C (PKC) activity, lipid composition or lipid metabolism. Dietary restriction of fat or carbohydrate energy (HFR or HCR group) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, cells from mice prefed the high corn oil diet for 10-13 weeks did not show an enhancement of PKC activity, but higher PKC activity was observed in energy-restricted mice fed a high corn oil diet than in control energy-restricted mice (18,31). In addition, modulation of PKC activity by energy restriction was observed in mice restricted for longer (10-13 wk), but not shorter (6-8 wk), periods of time (18). PKC-a in the particulate fraction of the epidermis of Sencar mice was not affected by prefeeding an energy-restricted diet for 6-12 weeks but was reduced 40% in the epidermis of mice prefed the diet for 13-29 weeks (11).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, cells from mice prefed the high corn oil diet for 10-13 weeks did not show an enhancement of PKC activity, but higher PKC activity was observed in energy-restricted mice fed a high corn oil diet than in control energy-restricted mice (18,31). In addition, modulation of PKC activity by energy restriction was observed in mice restricted for longer (10-13 wk), but not shorter (6-8 wk), periods of time (18). PKC-a in the particulate fraction of the epidermis of Sencar mice was not affected by prefeeding an energy-restricted diet for 6-12 weeks but was reduced 40% in the epidermis of mice prefed the diet for 13-29 weeks (11).…”
Section: Discussionmentioning
confidence: 91%
“…Elevated PKC activity was reported in epidermal cells from mice fed a high corn oil diet for six to seven weeks compared with cells from animals fed the control diet (14,30). However, cells from mice prefed the high corn oil diet for 10-13 weeks did not show an enhancement of PKC activity, but higher PKC activity was observed in energy-restricted mice fed a high corn oil diet than in control energy-restricted mice (18,31). In addition, modulation of PKC activity by energy restriction was observed in mice restricted for longer (10-13 wk), but not shorter (6-8 wk), periods of time (18).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We are aware of some discrepancies between our data and previously published literature. Kris et al found that calorie restriction increased total DG in the skin of SENCAR mice [ 21 ]. Our study, however, showed no change in total skin DG in calorie restricted mice and exercised and pair-fed mice when compared to controls ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies show that DG may also modulate Rho and Ras proteins [ 19 20 ]. Kris et al have shown an increase in epidermal DG following calorie restriction suggesting a connection between DG levels and energy balance [ 21 ].…”
Section: Introductionmentioning
confidence: 99%